(3MGTjI TGYQj Ydi MGTjI GdSjO Ydi TQM GdbWH Ydi GdTeSjIs - (3eLghds
(3ChdgG (B:s
(3HSe Gddg bGd GdeUfa QJHJg Ydi ebOeI hKdGK ebGdGJ hNGJeI , GYde Cf GdJQJjH dg eYGf KdGK GKfGf dZhjGf CMOgeG EjQGO TjA YbjH TjA BNQ hjSJYed jbGd QJHJJg Ydi cPG Cj ChQOJg YbjHg dG jecf Med GdJQJjH ggfG Ydi gPG GdeYfi (B...s
(3BNQgG (B:s
... (3bhdg hdhde jSde Cg` e Cf Pdc GdLhGH dG jOaY GdETcGd hefge ef bGd hgh GdeMcj dge de jQO GdeUfa HeG PcQg JYQja GdLRFj GdEVGaj Cj bUOG Hd CQGO PcQ Mce ef GMcGeg bUOG jecf Cf jSJfHW efg Gfg JYQja GdMGUd Gfg eKO GdJYQja JeJs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdadSaI hGdefWbs